2014
DOI: 10.1021/om5000198
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Mixed-Valent Ytterbium and Europium Complexes Supported by a Phenoxy(quinolinyl)amide Ligand

Abstract: The formation of mixed-valent ytterbium and europium complexes L4LnIII 2LnII (Ln = Yb (1), Eu (2)) was observed for the first time in the spontaneous reduction reaction system of quinolinyl aminophenol (H2L) with Ln[N(SiMe3)2]3 (Ln = Yb, Eu) in toluene at 90 °C, whereas the same reaction with Sm[N(SiMe3)2]3 gave the expected monoamido samarium complex LSmN(SiMe3)2(DME) (4). The isolation of the binuclear ytterbium complex L3Yb2 (3) under mild conditions demonstrates that the transformation from a trivalent ytt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…[18][19][20] Recently, we introduced this ligand system to organo-rare-earth chemistry, and a series of neutral and anionic phenoxy-amido rare-earth complexes were prepared conveniently by the direct amine elimination reaction between rareearth amide and aminophenols. [21][22][23][24] It was found that many phenoxy-amido organo-rare-earth complexes were efficient initiators for the ring-opening polymerization of lactides and cyclic carbonate. [21][22][23] To further expand the application of phenoxy-amido rare-earth complexes on homogeneous catalysis, a series of heterobimetallic rare-earth-lithium amido complexes stabilized by different aminophenoxo ligands (Chart 1) were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Recently, we introduced this ligand system to organo-rare-earth chemistry, and a series of neutral and anionic phenoxy-amido rare-earth complexes were prepared conveniently by the direct amine elimination reaction between rareearth amide and aminophenols. [21][22][23][24] It was found that many phenoxy-amido organo-rare-earth complexes were efficient initiators for the ring-opening polymerization of lactides and cyclic carbonate. [21][22][23] To further expand the application of phenoxy-amido rare-earth complexes on homogeneous catalysis, a series of heterobimetallic rare-earth-lithium amido complexes stabilized by different aminophenoxo ligands (Chart 1) were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from Figure C, the two energy levels severally split into two peaks, and the intensity of each front peak was higher than their respective rear peak, indicating the presence of two kinds of chemical state for Eu in L 4 Eu III 2 Eu II , and the Eu 3+ matching the peaks at 1133.5 and 1163.0 eV , contained 2.5 times as much as Eu 2+ matching the peaks at 1123.3 and 1155.0 eV, , in which their contents were 71.59 and 28.42%, respectively. These outcomes can be assumed to be due to the ligand redistribution reaction between Eu­[N­(SiMe 3 ) 2 ] 3 and complex L 3 Eu III 2 and the following partial reduction reaction: (i) the silylamine elimination reaction occurred between H 2 L and Eu­[N­(SiMe 3 ) 2 ] 3 accompanied by the production of binuclear complex L 3 Eu III 2 ; (ii) then, L 3 Eu III 2 reacted with Eu­[N­(SiMe 3 ) 2 ] 3 to acquire the trinuclear lanthanide amide (L 2 Eu) 2 EuN­(SiMe 3 ) 2 as the intermediate through a ligand redistribution reaction; and (iii) the fracture of Eu–N bonds contributed to the partial reduction of Eu 3+ to Eu 2+ , thus forming the mixed-valent trinuclear complex L 4 Eu III 2 Eu II , and in theory, the number of Eu 3+ should be twice that of Eu 2+ (Scheme A).…”
Section: Resultsmentioning
confidence: 99%
“…CYFRA 21-1 is a tumor marker, which is a full-length fragment of cytokeratins 19 distributed on the surface of normal tissues, such as lamellar or squamous epithelium. It possesses a major significance to productively monitor lung adenocarcinoma and lung squamous cell carcinoma and also breast, bladder, and ovarian cancer. , Among the as-fabricated biosensors, L 4 Eu III 2 Eu II as a signal probe was synthesized with a quinolinyl aminophenol ligand 3,5-Bu t 2 -2-(OH)­C 6 H 2 CH 2 NH-8-C 9 H 6 N (H 2 L) and Eu­[N­(SiMe 3 ) 2 ] 3 (μ-Cl)­Li­(THF) 3 relied on the amine elimination reaction, and the synthesis mechanism is shown in Scheme . The antenna effect that emerged from the two coordination environments ligand H 2 L with a strong conjugate effect conveyed energy to Eu 2+/3+ , and subsequently, Eu 2+ sensitized Eu 3+ , thus stimulating Eu 3+ to provide strength and steady luminescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no X-ray-diffraction-quality crystals were obtained for the [OC 4 F 9 ] − complexes 2-Ln (Ln = Eu, Gd, Dy), ESI-MS data are consistent with the assigned formulas for all. On the basis of the photoluminescence data (vide infra) and scarcity of nonpolymeric four-coordinate complexes of Eu, Gd, , and Dy ,, in the literature, it is proposed that 2-Ln also bears two THF ligands, as seen in 1-Ln , such that the solution structures are six-coordinate. In the absence of crystallographic data for 2-Ln , it is unknown whether the symmetry observed in 1-Ln , which results in only three unique Ln–O distances per complex, is maintained.…”
Section: Resultsmentioning
confidence: 99%